Back Cover: Predictive Value of Folate Receptor‐Positive Circulating Tumor Cells for the Preoperative Diagnosis of Lymph Node Metastasis in Patients with Lung Adenocarcinoma (Small Methods 6/2021). Issue 6 (10th June 2021) - Li, Zhao; Xu, Ke; Xu, Lekai; Dai, Jie; Jin, Kaiqi; Zhu, Yuming; Yang, Yang; Jiang, Gening
Abstract : In article number 2100152, Zhu, Yang, Jiang, and co‐workers from Shanghai Pulmonary Hospital established a noninvasive assessment of lymph node metastasis (LNM) in lung adenocarcinoma (LAD) through the detection of folate receptor‐positive (FR + ) circulating tumor cells (CTCs) methods. Preoperative FR + CTCs' detection showed good correlations with the number of positive lymph nodes (LNs) and the ratio of the number of positive LNs to removed LNs, having good prediction capacity and clinical application.